Observation of plastic packaging defects in halal chili sauce - Nur Hidayat, Rizky Priandi; Rahmadhia, Safinta Nurindra (Journal of Halal Science and Research, 2021)
Food packaging is a material used to contain or wrap food, both in direct and indirect contact with food. The packaging process is closely related to product quality to ensure that the process that occurs will produce products according to the specified standards and can prevent damage or packaging defects. The relationship between packaging defects also has an impact on consumer decisions when they want to buy a product. This is because of the first impression that consumers get after seeing the shape of the product packaging being sold. This study aims to determine the process that produces the most plastic packaging defects in the chili sauce production process and the conformity of plastic packaging quality standards with SNI. The process of observing the plastic packaging defects of chili sauce products on the machine is carried out within 7 days. The analysis method uses Pareto diagrams, pie charts, and control charts. The results obtained are the highest plastic packaging defects in the chili sauce production process, the highest on machine number 1 is 22% with the number of packaging defects being 170 pcs.